The role of AI-based tools in supporting reading development among learners with hearing disabilities: A narrative review - Abdul Rahman, Nur' Hamizah; Piragasam, Grace Annamal (Journal of Islamic, Social, Economics and Development, 2026)
This narrative review examines the role of Artificial Intelligence (AI) based tools in supporting reading development among learners with hearing disabilities, focusing on their potential, limitations, and future directions (Empowering Education: The Role of Artificial Intelligence in Supporting Students with Disabilities). Reading acquisition remains a significant challenge for this population due to reduced access to phonological awareness and auditory-based language cues, yet recent AI innovations, including speech-to-text systems, adaptive learning platforms, and natural language processing, offer promising solutions by providing personalized, multimodal, and accessible learning pathways. Literature was sourced from databases such as Scopus, Web of Science, ERIC, PubMed, and Google Scholar, using targeted search terms related to AI, hearing impairment, and literacy. Peer-reviewed studies in English from 2020 to 2025 were also included for analysis. Findings highlight that AI tools can enhance literacy through personalization, immediate feedback, and visual or text-based supports, though definitional inconsistencies, reliance on small-scale studies, affordability barriers, and ethical concerns, such as algorithmic bias, limit their broader application. The evidence suggests that hybrid approaches, combining teacher expertise with AI-driven personalization, may be the most effective strategy. However, long-term and large-scale outcomes remain underexplored. This review contributes to clarifying current opportunities and challenges, while also calling for more rigorous, culturally responsive research and for policymakers and practitioners to prioritize equitable access, teacher involvement, and ethical practices in implementing AI-driven literacy solutions.